2016 IEEE International Conference on Bioinformatics and Biomedicine (BIBM) 2016
DOI: 10.1109/bibm.2016.7822655
|View full text |Cite
|
Sign up to set email alerts
|

Periodicity intensity for indicating behaviour shifts from lifelog data

Abstract: Abstract-Periodic phenomena or oscillating signals can be found frequently in nature and recent research has observed periodicity appearing in lifelog data, the automatic digital recording of everyday activities. In this paper we are exploring periodicity and intensity of periodicity in big data settings, especially when the data is noisy, unevenly sampled and incomplete. An interesting possibility is to compute the intensity or strength of detected periodicity across the time span of a lifelog to see if it re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…Determining the intensity of 24 h periodicity over a time series of up to 8 weeks would result in a single periodicity intensity for weeks of data, which would not provide any insights into the behaviour during those weeks. Therefore, we used a sliding window of 7 days duration and determined the 24 h periodicity intensity for those 7 days, and then shifted it by 15 min before repeating the process across the next 7 days of data [ 16 ]. This time-lagged overlapping window across the entire data set for each calf provides intensity scores as schematically shown in Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Determining the intensity of 24 h periodicity over a time series of up to 8 weeks would result in a single periodicity intensity for weeks of data, which would not provide any insights into the behaviour during those weeks. Therefore, we used a sliding window of 7 days duration and determined the 24 h periodicity intensity for those 7 days, and then shifted it by 15 min before repeating the process across the next 7 days of data [ 16 ]. This time-lagged overlapping window across the entire data set for each calf provides intensity scores as schematically shown in Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Periodicity has been successfully applied in a number of fields including engineering, astronomy, biology, and physics [17]. In this paper we focus on the application of periodicity detection to time-series sensor data and we draw on our previous work in [8], [3] and [9]. In this previous work we applied periodicity analysis to accelerometer data captured from wrist-worn smart watches.…”
Section: Periodicity Analysis Of Sensor Datamentioning
confidence: 99%
“…In this previous work we applied periodicity analysis to accelerometer data captured from wrist-worn smart watches. In particular, [8] demonstrated that relevant periodicities can be detected from wrist-worn sensors, and we introduced the idea of measuring the intensity of periodicities over time. We contrasted six different methods for measuring the intensity of a periodicity, giving special consideration to irregularly-sampled data, and data that is missing large numbers of values.…”
Section: Periodicity Analysis Of Sensor Datamentioning
confidence: 99%
“…That work also found that high levels of periodicity indicating regular sleep and movement patterns were associated with lower measures of LDL-cholesterol, triglycerides and hs-CRP as well as improved health-related quality of life measures [9]. The same technique for visualising periodicity strength over time was used in an analysis of lifelog data defined as the automatic digital recording of everyday activities, and it provided insights into shifts in underlying behaviour of the subjects [10].…”
Section: Introductionmentioning
confidence: 98%